Dimensions of Lumbar Spinal Canal in subjects with and without low back pain - Irshad, Faiza; Ahmed, Sarfraz; Saeed, Haroon; Saleem, Anber; Abdullah, Muhammad Saad; Butt, Muhammad Tajammal; Nishat, Mufassar; Khan, Muhammad Afzal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Degenerative changes and mechanical stress lead to lumbar spinal canal stenosis resulting in low back pain. Various factors such as genetic, malnutrition, systemic disturbance and trauma may affect the size of lumbar spinal canal. Aim: To record the dimensions of lumbar spinal canal in symptomless adult male and female subjects and compare them with those with low back pain. Study design: Cross-sectional population study Study place Allama Iqbal Memorial Teaching Hospital Khawaja Muhammad Safdar Medical College, Sialkot Study duration February to November 2020 Material and methods: Anteroposterior and transverse diameters and cross sectional areas of the spinal canal were measured on CT scans using ImageJ1.47v at levels L1 to L5 in adult male and female subjects with and without low back pain. Results: Anteroposterior diameter was smaller at level L1in females with pain. Transvers diameter was significantly smaller in females with pain at L2, L3 and L5 and at L3-5 than in those without pain. Comparison of male subjects with and without pain showed significant difference at L5 while similar comparison was significant at L1 and L4 in the females. Highly significant difference (p < 0.0001) was observed at L2 to L5 among the males and L1 to L5 in the females when cross sectional areas were compared for the two groups. Conclusion: Subjects with pain had significantly lower values of various dimensions of the lumbar spinal canal in both sexes. The study has provided gender specific reference data which could be helpful in clinical assessment of spinal canal stenosis